Creating Healthy Golden Generation Without Cigarettes: Demarketing Strategy in Indonesia - Tielung, Maria V. (Archives of Business Research, 2021)
The millennial generation is the golden generation that will become the nation’s foundation and agents of change for a country. Creating a healthy golden generation is one of the requirements for an increase in the human development index of an area, which affects increasing the quality and quantity of this golden generation. The smoking lifestyle is one of the problems faced by the younger generation, and a solution must be found so that the dreams of a healthy young generation can be created. This paper is an empirical study that examines the demarketing strategy to reduce smoking lifestyles and intention to quit smoking among the younger generation. This research was conducted by surveying the Indonesian millennial generation with a sample in North Sulawesi Province. Data analysis using SEM analysis of the demarketing strategy model. This study provides an overview of the determinants of the demarketing strategy for the Millennial generation in Indonesia, namely the factors that affect the intention to quit smoking in the younger generation. The implications and limitations of the study are also discussed in this paper.